TINJAUAN PSIKOLOGIS TOKOH UTAMA NASKAH DRAMA SENJA DI TAMAN KARYA IWAN SIMATUPANG - Fifi Nola Sari; Yasnur Asri; Muhammad Ismail (Jurnal Bahasa dan Sastra, 2012)
This study aims to describe the psychologi calinner conflicts the main character is portrayed in drama Senja di Taman by Iwan Simatupang. The file of this study focused on the psychological main characters. Source of research file was dusk at the park plays works of Iwan Simatupang. File collected by (1) Read and understand the contents of Senja di Taman plays as a whole. (2) File inventory on the behavior of the main figures that show the inner conflict with the study of psychoanalysis. (3) Record the file on the chart recording. (4) Analyze and interpret file and conclusions.The findings of this study is the main characterin the drama script called OT (parents) use a third aspect of the id, ego, and superego. Her desiret of inda lost cat(id), OT does not claim his second wife for him (ego), more much silent and does not demand attention to the chil and this wife(superego).